Дарвийн бичээс - Ц.Баттулга (Acta Mongolica, 2009)
This runic inscription is located at the place called Baishin Uzuuriin Jurgeriin Tsagaan Tolgoi, at the end of Ats Bogd and Bumbat Bogd, which can be found in the Altaic Mountain range near the Darvi soum of the Khovd province. The inscription was studied previously by M. Shinekhuu and I.V. Kormushin.